User Testing to Drive the Iterative Development of a Strategy to Improve Implementation of Evidence-based Practices in School Mental Health. Issue 4 (1st October 2020) - Duong, Mylien T.; Cook, Clayton R.; Lee, Kristine; Davis, Chayna J.; Vázquez-Colón, Cheryl A.; Lyon, Aaron R.
ABSTRACT: Research has produced a steady stream of evidence-based practices (EBP) that can promote youth behavioral health, but widespread implementation is often poor. To narrow the "science to practice gap, " an implementation strategy was developed to enhance school-based mental health providers' intentions to implement EBP. The current study adopted a user-testing approach to inform the iterative development of this implementation strategy, which consisted of strategic education, social influence techniques, and motivational interviewing. Segments of the implementation strategy were demonstrated live for a representative sample of the intended audience. Participants rated each segment on acceptability, appropriateness, and likely impact on intentions to use EBP. Ratings were tallied in real-time and presented to participants to spur discussion. Qualitative input was coded via conventional content analyses. Results indicated that implementation strategies may need to be tailored to the specific EBP. In addition, implementation goal setting was well-received by some participants but not others, suggesting a difficulty of conducting motivational interviewing in group settings. Participants also perceived themselves as familiar with EBP and strong advocates of school mental health services. The paper concludes with a discussion of how this research has influenced the ongoing development of the strategy and implications for EBP implementation efforts.